Peran Teknologi Digital dalam Meningkatkan Kinerja Keuangan UMKM Rosendi Cake and Bakery - Fanolo Zega; Tri Maryani (Mahesa Research Center, 2026)
This article aims to analyze the role of digital technology in improving the financial performance of the UMKM Rosendi Cake and Bakery located in Klepu Village, Bergas District, Semarang Regency. The study focuses on how the utilization of digital technology contributes to increasing business revenue, marketing cost efficiency, and improvements in the financial management of UMKM. To address this issue, theoretical references related to digital marketing, business financial performance, and UMKM financial management are employed. This study adopts a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, direct observation, and documentation, and were analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the use of digital technology through social media, marketplaces, and business communication applications expands market reach and increases sales intensity, which in turn leads to revenue growth. Furthermore, digital technology utilization helps reduce marketing costs and improves the regularity of financial record-keeping. This study concludes that digital technology not only functions as a promotional tool but also serves as a strategic instrument in enhancing the financial performance, competitiveness, and sustainability of UMKM in the digital era.